Beating Naive Bayes at Taxonomic Classification of 16S rRNA Gene Sequences - Ziemski, Michal; Wisanwanichthan, Treepop; Bokulich, Nicholas A.; Kaehler, Benjamin D. (Frontiers in Microbiology, 2021)
Naive Bayes classifiers (NBC) have dominated the field of taxonomic classification of amplicon sequences for over a decade. Apart from having runtime requirements that allow them to be trained and used on modest laptops, they have persistently provided class-topping classification accuracy. In this work we compare NBC with random forest classifiers, neural network classifiers, and a perfect classifier that can only fail when different species have identical sequences, and find that in some practical scenarios there is little scope for improving on NBC for taxonomic classification of 16S rRNA gene sequences. Further improvements in taxonomy classification are unlikely to come from novel algorithms alone, and will need to leverage other technological innovations, such as ecological frequency information.